Measuring Methods of the Corporate Competitiveness, and Those Weaknesses - Orsolya, Nagy Tunde; Darabos, Eva; Labas, Istvan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
This treatise was carried out with the aim of giving the reader an overview of different conceptual approaches of the competitiveness. It particularly deals with the competitiveness according to the "practical" approach, "environmental/system" approach, "capital reorganisation" approach and with the widely accepted closed definitions of competitiveness. To determine the components of competitiveness according to different aspects, to assess some empirical examinations regarding the analysis of the aforementioned aspects as well as to present the results of an own primer research are also important parts of the treatise.